Exploration Of Sumedang Batik Binokasih Crown Motif For Official Events - Latif, B Syarifuddin; Asyari; Demolingo, Ramang H; Azahri, Alfin Fauzi (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
Sumedang is a city that makes batik cloth with special patterns depicting royal symbols, history, flora, and fauna of Sumedang Larang in Sumedang. The Binokasih crown motif is one of the typical Sumedang batik motifs, and it symbolizes the luxury, splendor, beauty, strength, and majesty of a king. Batik Mahkota Binokasih is applied to clothing for formal costumes in the Sumedang royal wedding attire style. Families with Sumedang royal ancestors usually wear the Sumedang royal wedding dress, and the Rama and Shinta wayang clothes inspire the pattern of this wedding dress. This research aims to create a new design as an official costume with Sumedang royal wedding attire using Sumedang batik material with the Binokasih crown motif.